Glutamate Receptor Homologs in Plants: Functions and Evolutionary Origins - Price, Michelle B.; Jelesko, John; Okumoto, Sakiko (Frontiers in Plant Science, 2012)
The plant glutamate receptors (GLRs) are homologs of mammalian ionotropic glutamate receptors (iGluRs) which were discovered more than 10 years ago, and are hypothesized to be potential amino acid sensors in plants. Although initial progress on this gene family has been hampered by gene redundancy and technical issues such as gene toxicity; genetic, pharmacological, and electrophysiological approaches are starting to uncover the functions of this protein family. In parallel, there has been tremendous progress in elucidating the structure of animal glutamate receptors (iGluRs), which in turn will help understanding of the molecular mechanisms of plant GLR functions. In this review, we will summarize recent progress on the plant GLRs. Emerging evidence implicates plant GLRs in various biological processes in and beyond N sensing, and implies that there is some overlap in the signaling mechanisms of amino acids between plants and animals. Phylogenteic analysis using glutamate receptors from metazoans, plants and bacteria showed that the plant GLRs are no more closely related to metazoan iGluRs as they are to bacterial glutamate receptors, indicating the separation of plant, eukaryotic, and bacterial GLRs might have happened as early on as the last universal common ancestor. Structural similarities and differences with animal iGluRs, and the implication thereof, are also discussed.